A Comparative Study to Understand the Efficiency of two Behavioral Change Communication Models Against Plastic Use - Khan, Aditi; Tripathy, Saswatik (Future Science / FSH-PH Publications, 2021)
The word pollution when comes to the mind feels dirty but people never think about how the surroundings are being polluted. If people want to get a clear environment, the behavioral change should be the first stepping stone. It is known to all that plastic is a non-biodegradable material but when talks about easily accessible material, mass production of plastic has been continued. Though different steps have been taken to ban the use of this harmful material every time failure has been observed. In this situation, behavioral change communication may help to solve this problem. Keeping all in the mind this particular study was conducted by two researchers in a particular block called Egra which is situated in West Bengal, India to understand the efficiency of the two models. Two different models have been applied viz. M1 and M2 and both work through a total of 6 stages. A total of 50 samples were taken and it was divided into two groups 25 each through the lottery method and applied the respective models. Through the study it has been observed that at the beginning periods success of the M1 model was good when 88% of people of M1 reach the contemplation period, another side only 52 percent of people reach the contemplation period of the M2 model. But slowly with time M2 also started to gear up and at the last, it achieves the same achievement as M1. This data proves that the M2 model is slow but steady. In the last stage, it was found that for M1 number of people in the contemplation period has increased to 60 percent people in the action and maintenance also decreased to 28 and 4 percent. Where in the case of M2 the people who are in action are 20 percent, 60 percent in the maintenance stage, and 20 percent population is terminated from this habit. In this stage, it is clear that the M2 has quite well retention power than the M1. Above all, it can be said that even M2 is slow though it is a better model than M1. Because at the end of the day it brings more numbers of terminated people. Later in the future by amalgamating these two models small weaknesses can be resolved, but for that, another detailed study has to be done.